Using Native-Speaker Psycholinguistic Norms to Predict Lexical Proficiency and Development in Second-Language Production. (13th March 2017) - Berger, Cynthia M; Crossley, Scott A; Kyle, Kristopher
Abstract: A large data set of L1 psycholinguistic norms (Balota et al. 2007 ) was used to assess spoken L2 English lexical proficiency in cross-sectional and longitudinal learner corpora. Behavioral norms included lexical decision and word naming latencies (i.e. reaction times) and accuracies for 40, 481 English words. A frequency measure was included to compare the relative strength of the norms to a traditional lexical measure when explaining proficiency and growth. The cross-sectional study revealed that learners identified as more lexically proficient by human raters produced words that were recognized more slowly and named more slowly and less accurately in L1 experimental settings. Moreover, lexical decision latencies explained more variance in ratings than frequency, while frequency and word naming latencies were comparable. The longitudinal study indicated that words produced by L2 speakers over time were recognized less accurately and named more slowly and less accurately by L1 subjects, while the frequency of those words decreased over time. Together, results demonstrate that L1 psycholinguistic information can index L2 lexical proficiency and growth across corpora while adding unique information to our understanding of L2 lexical knowledge.